2016
DOI: 10.5195/emaj.2016.92
|View full text |Cite
|
Sign up to set email alerts
|

Testing The ‘Black Swan Effect’ on Croatian Stock Market Between 2000 and 2013

Abstract: We tested the economic activity and stock exchange of Croatia as a new country of European Union (EU) in order to investigate the 'Black Swan effect' from 2000 to 2013. The empirical findings obtained in application of OLS methodology and Chow breaking point test provide evidence and show that resignation of the Croatian ex-Prime Minister did lead country successfully to EU. Also, 'The Black Swan' event, being unpredictable and having huge impact on political and economic environment in Croatia obtained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This statement is consistent with TAM, where perceived ease of use is an important determinant of adopting new technologies by individuals (Davis, 1989). Various studies have shown that the Effort Expectancy significantly influences an individual's intention to adopt a specific technology (Oliveira et al, 2016); (Peša & Brajković, 2016); (Slade, Dwivedi, Piercy, & Williams, 2015). Based on the explanation above: H2: Effort Expectancy has a significant positive effect on Behavioral Intention…”
Section: The Impact Of Effort Expectancy On Behavioral Intentionsupporting
confidence: 84%
See 1 more Smart Citation
“…This statement is consistent with TAM, where perceived ease of use is an important determinant of adopting new technologies by individuals (Davis, 1989). Various studies have shown that the Effort Expectancy significantly influences an individual's intention to adopt a specific technology (Oliveira et al, 2016); (Peša & Brajković, 2016); (Slade, Dwivedi, Piercy, & Williams, 2015). Based on the explanation above: H2: Effort Expectancy has a significant positive effect on Behavioral Intention…”
Section: The Impact Of Effort Expectancy On Behavioral Intentionsupporting
confidence: 84%
“…The stronger the perception that a particular technology is easy to learn and master, the stronger the person's interest in adopting the technology will be. This statement is in line with (Oliveira et al, 2016); (Peša & Brajković, 2016); and (Slade et al, 2015) Generation Z, known as the "Always-Clicking Generation," is a generation closely connected to the internet. This generation was born in the 1990s and grew up in the 2000s when the most significant change over the century came with the advent of the web, internet, smartphones, laptops, networks, and digital media (A. P. Singh & Dangmei, 2016).…”
Section: Si1mentioning
confidence: 53%
“…In the OECD countries, Kargi (2016) used the Engle-Granger Cointegration test to prove the Okun's Law existed in the twenty-three countries. It means that an increase in unemployment caused a decrease in the gross domestic product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it can be indicated that there is an uncertain relationship between the rate of unemployment and output in various countries. For example, the economic growth had a negative and significant effect on the unemployment rate (Abdul-Khaliq et al, 2014;Alamro & Al-dala'ien, 2016;Bande & Martın-RoMan, 2017;Blázquez-Fernández et al, 2018;Darman, 2013;Dritsaki & Dritsakis, 2014;Jibir et al, 2015;Kargi, 2016;Kori Yahia, 2018;Noor et al, 2007;Pierdzioch et al, 2011;Ruxandra, 2015;Soylu et al, 2018;Tatoglu, 2011;Zanin & Marra, 2012), the Okun's coefficient was not significant (Apergis & Rezitis, 2003;Arewa & Nwakanma, 2012;Astuti, 2016;Yaumidin, 2009), there were positive coefficients in the regression and it implied that the Okun's legal interpretation did not apply (Bankole & Fatai, 2013), there was no causality between economic growth and unemployment rate (Adeyeye et al, 2017), there was a two-way causality between unemployment and output growth (Boďa & Považanová, 2015;Noor et al, 2007), and the Okun's coefficient was different for each country (Azorín & de la Vega, 2017;Bande & Martın-RoMan, 2017;Dixon et al, 2016;Hutengs & Stadtmann, 2013;Moosa, 1997;Rahman & Mustafa, 2017;Silvapulle et al, 2004). Based on these findings, the following hypotheses was suggested:…”
mentioning
confidence: 99%
“…These big shifts in volatility seem to correspond with important country-specific political, social and economic events (Aggarwal et al, 1999). Peša and Brajković (2016) examine the economic activity and stock exchange of Croatia as a new country of EU to investigate the 'Black Swan effect' from 2000 to 2013. The empirical findings obtained in the employment of the OLS method and the Chow Breakpoint Test provided evidence and revealed that the resignation of the Croatian Ex-Prime Minister lead the country successfully to the EU, but also was a 'Black Swan event', having been unpredictable and resulting in a huge impact on the political and economic environment in Croatia as found through CROBEX, Croatian stock exchange indices.…”
Section: Introductionmentioning
confidence: 99%